FINANCING JUSTICE FOR SUSTAINABLE DEVELOPMENT IN MOLDOVA - Ludmila GONCEARENCO (Eastern European Journal of Regional Studies)
This paper provides a comprehensive analysis of the challenges and advancements in Moldova’s justice system reform, particularly in the context of achieving Sustainable Development Goals (SDGs). It delves into the pivotal role of the Moldovan justice system in governance and societal well-being, highlighting how its efficiency, transparency, and accessibility are essential for democracy, reducing corruption, and building public trust. The paper examines Moldova's ongoing struggles with judicial independence, corruption, and resource limitations, exacerbated by its post-Soviet transition and the need for alignment with European standards. The relevance of SDG 16, which focuses on promoting peaceful and inclusive societies, access to justice, and building effective institutions, is underscored as a key framework for Moldova’s judicial reforms. The paper argues that aligning Moldova’s justice system with SDG 16 is not only strategically necessary but also an ethical obligation. Improving the judicial system could lead to significant advancements in reducing corruption, enhancing public trust, and creating a stable legal environment conducive to economic growth and societal well-being. The paper also highlights the well-established link between an effective justice system and broader sustainable development goals in the literature. It includes a thorough literature review, analysis of justice financing in relation to SDGs, a discussion of Moldova's specific challenges, and concludes with policy recommendations and future research directions. This exploration aims to provide a nuanced understanding of Moldova's justice system reforms and their critical role in the nation’s journey towards sustainable development.